Indoor air quality : the latest sampling and analytical methods - Hess-Kosa, Kathleen (CRC Press, 2011)
In the new millennium, indoor air quality methodologies have expanded, evolved, and morphed. This book addresses the old and the new. The focus is shifting from a knee-jerk to a more proactive response. Although indoor air quality in older buildings will continue to present old challenges, new construction is going forward with new challenges. Indoor Air Quality: The Latest Sampling Methods, Second Edition covers basic concepts and details various approaches to the identification and assessment of indoor air contaminants that contribute to building-related ill.
Keywords: Indoor air pollution -- Measurement.; elektronické knihy; electronic books